Implementation evaluation and refinement of an intervention to improve blunt chest injury management—A mixed‐methods study. Issue 23 (18th April 2017) - Curtis, Kate; Van, Connie; Lam, Mary; Asha, Stephen; Unsworth, Annalise; Clements, Alana; Atkins, Louise
Abstract : Aims and objectives: To investigate uptake of a Chest Injury Protocol (ChIP), examine factors influencing its implementation and identify interventions for promoting its use. Background: Failure to treat blunt chest injuries in a timely manner with sufficient analgesia, physiotherapy and respiratory support, can lead to complications such as pneumonia and respiratory failure and/or death. Design: This is a mixed‐methods implementation evaluation study. Methods: Two methods were used: (i) identification and review of the characteristics of all patients eligible for the ChIP protocol, and (ii) survey of hospital staff opinions mapped to the Theoretical Domains Framework (TDF) to identify barriers and facilitators to implementation. The characteristics and treatment received between the groups were compared using the chi‐square test or Fischer's exact test for proportions, and the Mann–Whitney U‐test for continuous data. Quantitative survey data were analysed using descriptive statistics. Qualitative data were coded in NVivo 10 using a coding guide based on the TDF and Behaviour Change Wheel (BCW). Identification of interventions to change target behaviours was sourced from the Behaviour Change Technique Taxonomy Version 1 in consultation with stakeholders. Results: Only 68.4% of eligible patients received ChIP. Fifteen facilitators and 10 barriers were identified to influence the implementation of ChIP in the clinical setting. These themes were mapped to 10 of the 14 TDF domains and corresponded with all nine intervention functions in the BCW. Seven of these intervention functions were selected to address the target behaviours and a multi‐faceted relaunch of the revised protocol developed. Following re‐launch, uptake increased to 91%. Conclusions: This study demonstrated how the BCW may be used to revise and improve a clinical protocol in the ED context. Relevance to clinical practice: Newly implemented clinical protocols should incorporate clinician behaviour change assessment, strategy and interventions. Enhancing the self‐efficacy of emergency nurses when performing assessments has the potential to improve patient outcomes and should be included in implementation strategy.